Contacto social de estudiantes universitarios con indígenas chilenos: estructura y asociaciones con estereotipos - Salazar-Fernández, Camila; Saiz, José L. (Pontificia Universidad Católica del Perú, 2024)
In non-indigenous Chilean university students, this study examined (1) the two-dimensional structure (quantity and quality) of social contact with the Mapuche people, and (2) the associations of these dimensions with stereotypes attributed to this group in a context of interethnic conflict. A purposive sample of 332 participants reported on their contact with the Mapuche, both in quantity and quality, and their adherence to various positive and negative stereotypes about this outgroup. The results supported an oblique factorial structure of contact (quantity and quality), revealing significant correlations between these factors and the stereotypes. Importantly, the quality of contact demonstrated more intense associations with stereotypes compared to its quantity. The latent interaction between quantity and quality did not significantly impact stereotypes. The study highlights the need to differentiate quantity and quality of contact when examining their relationships with other psychosocial constructs.

Este estudio examinó en estudiantes universitarios no indígenas chilenos (1) la estructura bidimensional (cantidad y calidad) del contacto social con indígenas mapuches y (2) las asociaciones de estas dimensiones con los estereotipos adscritos a este pueblo originario, en un contexto de conflicto interétnico. Una muestra intencionada de 332 participantes reportó la cantidad y calidad de su contacto con mapuches, así como su nivel de adhesión a distintos estereotipos positivos y negativos sobre este exogrupo. Los resultados corroboraron una estructura factorial oblicua del contacto (cantidad y calidad) y revelaron correlaciones significativas entre estos factores y los estereotipos, mostrando la calidad del contacto, comparada con la cantidad del mismo, asociaciones más intensas. La interacción latente entre la cantidad y la calidad no mostró un efecto significativo sobre los estereotipos. Este estudio destaca la necesidad de distinguir entre cantidad y calidad del contacto al analizar sus relaciones con otros constructos psicosociales.

Cette étude a examiné chez des étudiants universitaires chiliens non indigènes (1) la structure bidimensionnelle (quantité et qualité) des contacts sociaux avec les indigènes mapuches et (2) les associations de ces dimensions avec les stéréotypes attachés à ce peuple indigène, dans un contexte de conflit interethnique. Un échantillon raisonné de 332 participants a rapporté la quantité et la qualité de leurs contacts avec les Mapuches, ainsi que leur niveau d’adhésion à différents stéréotypes positifs et négatifs sur cet ex-groupe. Les résultats ont corroboré une structure factorielle oblique des contacts (quantité et qualité) et ont révélé des corrélations significatives entre ces facteurs et les stéréotypes, la qualité des contacts montrant des associations plus fortes que la quantité des contacts. L’interaction latente entre la quantité et la qualité n’a pas montré d’effet significatif sur les stéréotypes. Cette étude souligne la nécessité de distinguer la quantité et la qualité des contacts lors de l’analyse de leurs relations avec d’autres construits psychosociaux.

Neste estudo, em universitários chilenos não indígenas, examinou-se (1) a estrutura bidimensional (quantidade e qualidade) do contato social com os Mapuche e (2) as associações destas dimensões com estereótipos atribuídos a este grupo em um contexto interétnico. Uma amostra de 332 participantes relatou seu contato com os Mapuche e a aderência a estereótipos positivos e negativos. Os resultados apoiaram uma estrutura fatorial oblíqua do contato, revelando correlações significativas entre estes fatores e estereótipos. A qualidade do contato mostrou associações mais intensas com estereótipos do que a quantidade. A interação latente entre quantidade e qualidade não afetou significativamente os estereótipos. O estudo sublinha a necessidade de diferenciar quantidade e qualidade do contato ao examinar suas relações com outros construtos psicossociais.
University students’ social contact with Chilean indigenous people: structure and associations with stereotypes
Contact social d’étudiants universitaires avec des indigènes chiliens: Structure et associations avec les stéréotypes
Keywords: Intergroup contact; Stereotypes; University students; Chilean indigenous people; Intergroup conflict; Contacto intergrupos; Estereotipos; Estudiantes universitarios; Indígenas chilenos; Conflicto intergrupos; Contacts intergroupes; Stéréotypes; Étudiants universitaires; Indigènes chiliens; Conflits intergroupes; Contato intergrupal; Estereótipos; Estudantes universitários; Indígenas chilenos; Conflito intergrupal; https://purl.org/pe-repo/ocde/ford#5.01.00